2017
DOI: 10.1161/circulationaha.117.029557
|View full text |Cite|
|
Sign up to set email alerts
|

C1q/Tumor Necrosis Factor–Related Protein-9 Regulates the Fate of Implanted Mesenchymal Stem Cells and Mobilizes Their Protective Effects Against Ischemic Heart Injury via Multiple Novel Signaling Pathways

Abstract: Background Cell therapy remains the most promising approach against ischemic heart injury. However, the poor survival of engrafted stem cells in the ischemic environment limits their therapeutic efficacy for cardiac repair post myocardial infarction (MI). C1q/tumor necrosis factor–related protein-9 (CTRP9) is a novel pro-survival cardiokine with significantly downregulated expression after MI. Here, we tested a hypothesis that CTRP9 might be a cardiokine required for a healthy microenvironment promoting implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 36 publications
4
96
0
Order By: Relevance
“…Numerous studies have identified various pathological factors involved in the pathological process, including mitochondrial dysfunction, inflammatory response, endoplasmic reticulum stress, and oxidative stress . Despite extensive efforts having been put into the research of myocardial infarction and ischemic reperfusion injury, there still existed little effective treatment and intervention target …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have identified various pathological factors involved in the pathological process, including mitochondrial dysfunction, inflammatory response, endoplasmic reticulum stress, and oxidative stress . Despite extensive efforts having been put into the research of myocardial infarction and ischemic reperfusion injury, there still existed little effective treatment and intervention target …”
Section: Introductionmentioning
confidence: 99%
“…10 Despite extensive efforts having been put into the research of myocardial infarction and ischemic reperfusion injury, there still existed little effective treatment and intervention target. 11 Long non coding RNA (LncRNA) is a series of non coding RNA that is longer than 200 nt and is not coding protein. 12 LncRNA has been well-studied in different diseases, including cerebral stroke, 13 heart development, 14 and tumor development.…”
mentioning
confidence: 99%
“…Adipose‐derived mesenchymal stem cells were isolated from inguinal subcutaneous adipose tissue as previously described . Briefly, adipose tissues were cut into small pieces in phosphate‐buffered saline (PBS) on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies utilizing MSCs have been conducted, being considered a promising treatment for ischaemic tissue injuries, such as hindlimb ischaemia and myocardial infarction . Due to the simplicity and reproducibility of the isolation process, adipose tissue has become an attractive source of MSCs for regenerative medicine . In recent years, multiple studies have been performed to use adipose‐derived mesenchymal stem cells (ADSCs) for the revascularization and tissue repair of ischaemic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Our efforts to identify novel regulators of metabolism have led to the identification and characterization of C1q/TNF-related proteins (CTRP1-15), secreted proteins of the C1q family conserved from fish to human. [6][7][8] In vivo animal studies highlight important metabolic, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] cardiovascular, [26][27][28][29][30][31][32][33][34][35][36] and inflammatory 12,13,[37][38][39][40] functions for multiple family members.…”
Section: Introductionmentioning
confidence: 99%